PELATIHAN DASAR PEMROGRAMAN PYTHON UNTUK MENINGKATKAN LITERASI DIGITAL DI SEKOLAH SMK ADVENT BATAM - Hotma Pangaribuan; Sunarsan Sitohang (JUPADAI : Jurnal Pengabdian Kepada Masyarakat, 2025)
Basic Python programming training at Batam Adventist Vocational School aims to improve students' digital literacy to prepare them for the information technology era. This activity was motivated by students' low understanding of programming and the need for digital skills in the workplace. The implementation method was carried out through face-to-face workshops, hands-on practice, and simple project-based evaluations. The results showed a significant increase in students' understanding of basic Python concepts, logical skills, and motivation to learn programming further. This training is expected to be the first step in building a technology-literate generation ready to face the challenges of the Industrial Revolution 4.0.